(untitled) (The Peerian Journal, 2023)
The main idea of every artist’s works is the issue of bringing up mature and versatile young people. He is mainly brought up in the family environment and is formed as a person. Education is considered the most important pillar of life. It will be discussed about the life and creative path of Abdulla Avloni.